2018
DOI: 10.17759/pse.2018230508
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Processing of Social Information in Internet and Features of Moral Consciousness in Adolescents

Abstract: Рассматривается актуальная тема связи информационной социализации с моральным развитием подростков . Выделяется роль способов когнитивной переработки социальной информации (КПИ) в процессе развития морального сознания детей . Исследование направлено на изучение взаимосвязи КПИ интернет-сети и формирования представлений подростков о моральной регуляции отношений в современном информационном обществе . Выборку составили 208 подростков . Выделено три типа КПИ, различающихся по целостности восприятия и интерпретац… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Sattarova's dissertation is devoted to the pedagogical conditions for ensuring the information security of students using the Internet in education [8]. The social and psychological perspective of teenagers and teachers on the Internet environment [9,10,11]. The information and psychological security of a person is considered by us as a set of internal personal resources (emotional, cognitive, value-based), mechanisms of psychological defense against destructive information [1].…”
Section: Methodsmentioning
confidence: 99%
“…Sattarova's dissertation is devoted to the pedagogical conditions for ensuring the information security of students using the Internet in education [8]. The social and psychological perspective of teenagers and teachers on the Internet environment [9,10,11]. The information and psychological security of a person is considered by us as a set of internal personal resources (emotional, cognitive, value-based), mechanisms of psychological defense against destructive information [1].…”
Section: Methodsmentioning
confidence: 99%
“…The severity of Internet addiction reduces the effectiveness of online cognitive assessment of social information. Based on the analysis of the data obtained, three types of cognitive processing of information were identified, each differing in the efficacy of perception realization and information decoding, its interpretation, goal clarification, assessment of short-term, medium-term and long-term prospects for action and behavioral reactions and the ability to differentiate and choose adequate social behavioral forms (Molchanov et al, 2018). We believe the moral regulation of behavior to be associated with the specifics of cognitive processing of social information (Molchanov, 2007).…”
Section: Problem Statementmentioning
confidence: 99%
“…Internet communication, like any form of interaction, takes place in the value-moral normative space of moral regulation, in which the nature of moral self-regulation both prevents and provokes the risks of encountering situations of a partner's deviant behavior, cyber bullying, and various online risks (Voiskounsky, 2017). Since the Internet and social media today constitute a major source of information that defines modern adolescents' world assumptions, their moral consciousness and ideas about justice, moral responsibility and duty become associated largely with the cognitive methods of social information processing (Molchanov, Almazova, Poskrebisheva, & Kirsanov, 2018). Analysis of the features of cognitive methods of processing information in social media poses an important challenge precisely in adolescence, which tends to make teens conform to the opinions of others, especially their peers (Lansford et al, 2006;Kupersmidt, Stelter, & Dodge, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…If a balanced type of psychological well-being is characterized by a high level of moral judgment and the efficiency of processing social information, then the ego-centered type reveals lowlevel moral judgment, self-orientation and self-interest, low effectiveness of cognitive methods of processing social information with severity of symptoms of Internet addiction. Molchanov et al (2018) revealed the relationship between cognitive ways of processing social information of the Internet network and the features of moral consciousness and ideas about moral regulation, responsibility and moral sensitivity. Preference for moral judgments of the post-conventional level, willingness to recognize moral responsibility in a situation of violation of moral norm, sensitivity to the moral content of communication and interpersonal interaction are observed in adolescents with high efficiency of cognitive processing of information.…”
Section: Introductionmentioning
confidence: 99%